Unveiling the determinants of climate change adaptation among small Landholders: Insights from a Mountainous Region in Pakistan - Iftikhar Ali; Ashfaq Ahmad Shah; Bader Alhafi Alotaibi; Chong Xu; Amjad Ali; Yousuf Ali (Climate Services)
Small landholders in Pakistan’s high mountainous regions face significant challenges in adapting to the impacts of climate change. This study investigates the adaptation strategies employed by smallholder farmers to address these challenges and identifies the household-level factors influencing these strategies in Nagar Valley. Using a quantitative approach, data were collected through a structured survey involving 430 households. Data are analyzed using bivariate and probit regression models. The study reveals that smallholder farmers adopt various strategies to cope with climate change, including using chemical fertilizers, pesticides, and insecticides, practicing crop rotation, and transitioning to horticulture. The findings of the multivariate probit model demonstrate a significant association between age, gender, education, and the likelihood of adopting adaptation strategies. The study advocates for developing context-specific climate adaptation strategies tailored to these regions’ unique agroecological zones to enhance small landholders’ resilience against climate change impacts. It also emphasizes the need to raise awareness among smallholders about modern, climate-smart agricultural practices and adaptive strategies.